REGIONAL CAPACITY FOR DISASTERS IN NORTH MINAHASA REGENCY (Case Study: Kec. Likupang Timur, Kec. Likupang Barat, Kec. Kema) - Rifay, Ranifa S; Takumansang, Esli D; Kapugu, Herry (SPASIAL, 2021)
Increasing regional capacity for disasters is one of the most important efforts to reduce the impact of disasters. Because most areas in Indonesia are inseparable from various types of natural disaster threats. Based on the disaster risk index by the Regional Disaster Management Agency of North Minahasa Regency, it was identified that the East Likupang District, West Likupang District, and Kema District have the potential for flooding and tsunami disasters. The purpose of this study is to identify the distribution of areas prone to floods and tsunamis in each research area, and to measure the level of regional capacity to disaster in the research area through capacity assessment criteria. The method used is qualitative analysis method and quantitative descriptive method for assessing the level of capacity in North Minahasa District, especially in East Likupang District, West Likupang District, and Kema District against disasters. The results of the analysis show that from the 5 assessment criteria it has been found that in each sub-district has a "MEDIUM" level of regional capacity. With the assessment of regional capacity, it is possible to know that the community is prepared to survive when a disaster occurs. Keywords : Regional Capacity, Disaster